Supply Chain Analysis of Farmed Exotic Carps in Jammu and Kashmir, India - Nisar, Ubair; Kumar, Nalini Ranjan (Fishery Technology, 2018)
The study was conducted in the state of Jammuand Kashmir where the major fish marketingstakeholders like fish farmers, pre-harvestingcontractors, wholesalers, retailers and fish vendorswere interviewed. In Jammu and Kashmir theculture of exotic carps like grass carp(Ctenopharyngodon idella) (Steindachner, 1866), silvercarp (Hypophthalmichthys molitrix) (Valenciennes,1844) and common carp (Cyprinus carpio)(Linnaeus, 1758) is carried out and the culture hasproved to be economical. The disposal pattern ofthe exotic carp revealed that the overall localconsumption of the fish by the farmers in the statewas less around 3.79% only as it was a source oflivelihood, so farmers preferred to sell rather thanconsuming themselves. The most significant effecton the marketing costs of the locally cultured exoticfishes was observed by the use of excess casuallabours and water charges. There were three majorSupply Chains (SC) prevailing in the state (SC I,SC II and SC III) and amongst them the marketingchannel III was most efficient (17.82) with highestproducers share in consumer’s rupee (94.69) wherethe farmers were directly selling the production tothe consumers. The state was not self-sufficient inmeeting the demands of the people so fishesproduced in other states were also marketed.